Retail transformation concepts development under the influence of industrial revolutions - L. S. Klimchenia (Вестник университета)
The relevance of the study is due to the lack of works on industrial revolutions impact on retail trade and transformation of its concepts.   The purpose of the study is to analyze industrial revolutions impact on retail trade and its transformation concepts development.   The methods of induction, deduction, comparison, and system analysis were used as a methodological basis. As part of the research, the author has generalized the results of scientific works in the field of technological development and the change of industrial revolutions and technological innovations impact on retail trade. The basic characteristics of industrial revolutions have been proposed such as onset conditions and results, their time boundaries, and the technological modes corresponding to them. The achievements of each industrial revolution are used in economy, causing a chain reaction in its branches. Retail trade is presen ted as a secondary segment of technological innovation implementation in relation to industry. At the same time, it has undergone the same stages of transformation as industry. The author has identified five concepts of retail trade, substantiated the transition timeframes to them, and cited the trade service transformation factors. The author substantiates that during the industrial revolutions change the content of the trade process does not change, but the resources that ensure its implementation are transformed in order to improve trade services quality to population.